2008
DOI: 10.2478/s11536-008-0001-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of two protocols for sedation in pediatric oncology procedures

Abstract: AbstractInvasive procedures, such as the lumbar puncture, can cause anxiety and pain in children undergoing treatment for acute lymphoblastic leukemia (ALL). We investigated the safety and efficacy of two different protocols for pain relief in 20 children with ALL undergoing lumbar puncture. Protocol A was composed of an association between propofol and alfentanil. Protocol B consisted in the combination of propofol and ketamine. Vital and behavioural parameters, sedation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The use of preprocedural opioids is strongly associated with an increased risk of an adverse event regardless of the sedation drug used [17]. A study conducted by Crea et al compared the incidence of adverse effects caused by propofol and alfentanil with propofol and ketamine, and their study findings suggested that although there are some adverse effects associated with propofol and ketamine, their use is much safer than the other combination and recommended its use in these patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…The use of preprocedural opioids is strongly associated with an increased risk of an adverse event regardless of the sedation drug used [17]. A study conducted by Crea et al compared the incidence of adverse effects caused by propofol and alfentanil with propofol and ketamine, and their study findings suggested that although there are some adverse effects associated with propofol and ketamine, their use is much safer than the other combination and recommended its use in these patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol induces dose-dependent cardiovascular and respiratory depression [7]. The rapid titrability, brief pharmacologic effect, and maintenance of spontaneous ventilation make intravenous propofol a suitable agent for conscious sedation during MES when patient cooperation is necessary (e.g., for evaluation of hearing).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study compared groups that received propofol and ketamine or propofol and alfentanil and the need for additional propofol was less in the ketamine group. [6] These results show that the ketamine-propofol combination provides more effective sedation. The authors did not find a significant difference between the groups despite a longer time to awakening in the group administered ketamine.…”
Section: Discussionmentioning
confidence: 83%
“…The authors did not find a significant difference between the groups despite a longer time to awakening in the group administered ketamine. [6] Tian and his friends found the longest recovey period to be 5 minutes in their studies which had the subject of children who were diagnosed with leukemia and who were administered fentanyl propofol combination for sedation. [12] In our study, there is no difference with regard to recovery time which is 5.1 minutes for the group F and 5.5 minutes for group K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation